Mineral nitrogen associated changes in growth and Xylem-N compounds in amazonian legume tree - Omena-Garcia, Rebeca Patricia; Justino, Gilberto Costa; Ferreira de Araujo, Vanderlei Borboni; Gomes de Souza, Luiz Augusto; Camargos, Liliane Santos de [UNESP]; Carvalho Goncalves, Jose Francisco de (Taylor & Francis Inc, 2015)
In nodulated young Inga edulis plants, nodule and plant growth, nitrogen (N) in xylem sap and tissues total contents of amino acid, ureide, and nitrate were determined in response to nutrition with nitrate, ammonium, or no mineral N. Additionally, the amount of soluble sugars in the different plant tissues was quantified. It was found that mineral N improved plant growth in height and diameter especially with ammonium. However, nitrate dramatically reduced nodule dry weight on a root dry weight basis and impaired N organic transport by xylem sap. Additionally, a higher amount of amino acids was observed in the roots and nodules of plants fed with mineral N but sugar levels remained constant. Although nitrate inhibited symbiosis, data support the idea that I. edulis is able to use both molecular and mineral nitrogen during the life cycle.
Keywords: Tropical tree species; Glutamine; Symbiosis; Xylem nitrogen flux; Nitrogen symbiotic fixation; Nodulation